Interactive documentary as a living and embodying experience to represent reality: A practice-based case study - Hsham Aburghif (CINEJ Cinema Journal)
This article introduces an innovative approach to comprehending the portrayal of reality within interactive documentaries. Drawing upon my filmmaking expertise, I created the interactive documentary Eden Again to examine how this multimedia genre portrays our understanding of a location, cultures, and social bonds by representing the controversial stories of drying the Marshlands of Iraq. This study also aims to enhance audience involvement, influencing contemporary media culture. These insights stem from a practice-based case study and contribute to the ongoing discussion about the representation of reality. The results indicate that users/viewers generally held favourable perceptions and attitudes toward the positive impacts of interactive documentaries, anticipating a positive reflection on this location.